(untitled) (Altre Modernità, 2025)
In 2018, Mexican author Gabriela Jáuregui coordinated a book under the title Tsunami, with the participation of fundamental voices of Mexican letters such as Yásnaya Elena A. Gil, Margo Glantz, Cristina Rivera Garza, Vivian Abenshushan or Verónica Gerber Bicecci. A year later, Marta Sanz coordinated the Spanish version of this Tsunami, with the participation of authors such as Cristina Fallarás, Sara Mesa, Cristina Morales or Laura Freixas. In this text we will ask ourselves which are the influences of feminisms between Spain and Mexico. We will emphasize the fundamental importance that Latin American feminisms have had in the configuration of the Spanish feminist panorama and we will delve into the idea that the feminist struggle cannot be considered only at a national level, but that there is a flow of waves, an ideological evolution without which it would not have been possible to achieve the articulated struggle that we have been witnessing in recent years.